Engineering Photoresponsive Ligand Tethers for Mechanical Regulation of Stem Cells. Issue 48 (24th September 2021) - Zhang, Junsheng; Wong, Siu Hong Dexter; Wu, Xin; Lei, Hai; Qin, Meng; Shi, Peng; Wang, Wei; Bian, Liming; Cao, Yi
Abstract: Regulating stem cell functions by precisely controlling the nanoscale presentation of bioactive ligands has a substantial impact on tissue engineering and regenerative medicine but remains a major challenge. Here it is shown that bioactive ligands can become mechanically "invisible" by increasing their tether lengths to the substrate beyond a critical length, providing a way to regulate mechanotransduction without changing the biochemical conditions. Building on this finding, light switchable tethers are rationally designed, whose lengths can be modulated reversibly by switching a light‐responsive protein, pdDronpa, in between monomer and dimer states. This allows the regulation of the adhesion, spreading, and differentiation of stem cells by light on substrates of well‐defined biochemical and physical properties. Spatiotemporal regulation of differential cell fates on the same substrate is further demonstrated, which may represent an important step toward constructing complex organoids or mini tissues by spatially defining the mechanical cues of the cellular microenvironment with light. Abstract : A strategy is developed to regulate the behaviors and functions of stem cells by switching the states of light‐switchable tethers. This method offers the chance to study mechanotransduction via cellular tethers and realize spatiotemporal regulation of differential cell fates.